The Implementation of Religious Tolerance: Study on Pesantren Bali Bina Insani with Bali Hindus Communities - Aryati, Ani; Suradi, A. (SCAD Independent, 2022)
This study aimed to describe the learning of religious tolerance in Bali Bina Insani Islamic Boarding School and its implications from an Islamic perspective. The research method used was qualitative, descriptive, phenomenological, and normative. Bali Bina Insani Islamic Boarding School has a harmonious interaction with the surrounding community, Hindus, and involves several Hindu teachers teaching at the Islamic boarding school. Bali Bina Insani Islamic Boarding School has practiced tolerance between religious believers, and even another Islamic boarding school still speaks of tolerance as ideas and ideals, but religious tolerance in this Islamic boarding school is a fact. This Islamic Boarding School does not emphasize differences but similarities in carrying out daily activities. The students come into direct contact with the Hindu community and experience the value of tolerance, interact with people of different religions and learn to absorb the meaning of mutual understanding and respect for one another without unduly emphasizing differences. The life of interfaith tolerance in Bali's Islamic Boarding School Bina Insani is a development of the principle of tolerance education that adopts the values ​​contained in the sources of Islamic teachings, namely the Koran and Hadith.